CREATIVE AND INNOVATIVE POTENTIAL OF LEAN-PRODUCTION DEVELOPMENT PHILOSOPHY AS A FACTOR OF SUSTAINABLE PRODUCTION - Vìtalina Nikitenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
This concept leverages the creative and innovative potential of production, spreading it to employees, distributors and suppliers, so that there are no problems among the subjects of this process. It is emphasized that most of the lean tools present a real challenge to the business executives, who are needed to improve product development, supply chain management, production operations and customer relationships. The new concept of "lean manufacturing" can direct the entire flow of "valueseeking" to the pursuit of excellence.